2007
DOI: 10.1007/s10529-007-9548-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved salt tolerance in tobacco plants by co-transformation of a betaine synthesis gene BADH and a vacuolar Na+/H+ antiporter gene SeNHX1

Abstract: Three types of transgenic tobacco plants were acquired by separate transformation or co-transformation of a vacuolar Na(+)/H(+) antiporter gene, SeNHX1, and a betaine synthesis gene, BADH. When exposed to 200 mM NaCl, the dual gene-transformed plants displayed greater accumulation of betaine and Na(+) than their wild-type counterparts. Photosynthetic rate and photosystem II activity in the transgenic plants were less affected by salt stress than wild-type plants. Transgenic plants exhibited a greater increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 22 publications
5
53
0
1
Order By: Relevance
“…Our data also revealed that glycine betaine accumulation is induced by salt treatment. The protective role of betaine may lie in its strong stabilizing effects on the structure and function of the oxygenevolving PSII complex (Ohnishi and Murata, 2006;Zhou et al, 2008). This is consistent with transgenic plants containing high betaine levels having enhanced tolerance to abiotic stress.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our data also revealed that glycine betaine accumulation is induced by salt treatment. The protective role of betaine may lie in its strong stabilizing effects on the structure and function of the oxygenevolving PSII complex (Ohnishi and Murata, 2006;Zhou et al, 2008). This is consistent with transgenic plants containing high betaine levels having enhanced tolerance to abiotic stress.…”
Section: Discussionsupporting
confidence: 60%
“…Glycine betaine protects the plant from salt stress by maintaining the osmotic balance under various abiotic stresses (Wani et al, 2013) and by stabilizing the quaternary structure of complex proteins (Bernard et al, 1988). In photosynthetic systems, glycine betaine stabilizes the oxygen-evolving photosystem II complex and Rubisco at elevated salt concentrations (Zhou et al, 2008;Fan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The coexpression of Na ϩ /H ϩ antiporters with genes of the GB biosynthetic pathway has the potential to increase salt tolerance by many times. Recently, co-transformation of the Na ϩ /H ϩ antiporter gene (SeNHX1) and BADH was reported in tobacco (Zhou et al 2008). The resulting transgenic plants accumulated more GB and showed higher biomass than either the single-gene transgenic plants or untransformed controls.…”
Section: Discussionmentioning
confidence: 99%
“…1 Evidences in the NHX1 transgenic plants and yeasts support the enhanced tolerance to salt stress by overexpressing Na C /H C exchangers. [2][3][4] Recent studies suggest NHX1 affect the lumen pH 5 by regulating H C transportation, which is associated with cellular ROS metabolism. [6][7][8] In our previous study, we found NHX1 could regulate cellular ROS level, and participate in plant disease defense.…”
mentioning
confidence: 99%
“…9 However, no evidence demonstrates that transformation of NHX1 could improve both salt tolerance and disease defense in plant. In this study, the T1 progenies of Nicotiana tabacum L. (Wisconsin 38) lines expressing SeNHX1 (from Salicornia europaea) were generated, 4 which were used to investigate the resistance to Phytophthora parasitica var nicotianae (Ppn) and the salt tolerance.…”
mentioning
confidence: 99%